1993
DOI: 10.1246/bcsj.66.3241
|View full text |Cite
|
Sign up to set email alerts
|

Spectra Analysis of the XPS Core and Valence Energy Levels of Polyvinyl Alcohol by an ab initio MO Method Using the 1,3,5-Hexanetriol Molecule

Abstract: The X-ray photoelectron spectra of polyvinyl alcohol (PVA) were analyzed by an ab initio MO method using the 1,3,5-hexanetriol (HTO) molecule. The theoretical spectral patterns derived from the Gelius–Siegbahn model showed good agreement with the spectra observed between 0—30 eV. The present results suggest several new assignments for the XPS spectra. The core-level C1s peaks at 285.0 and 286.5 eV correspond to the C1s electron levels arising from the CH2 and CH(OH) groups, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

1994
1994
2000
2000

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 11 publications
0
2
1
Order By: Relevance
“…Recently, Delhalle et al 24 found evidence of a folded structure at the surface of polyethylene lamellae in the XPS valence band. In our previous papers, [16][17][18]20 we used syndiotactic model molecules for analysis of XPS of polymers, because we found that the tacticity had little effect on the calculated energy structure, in contradiction to the results of other workers. 23,24 In previous studies, [19][20][21][22] we showed that earlier workers used Koopmans' theorem and the δ-SCF method to analyze the photoelectron spectra of polymers.…”
Section: Introductioncontrasting
confidence: 56%
See 2 more Smart Citations
“…Recently, Delhalle et al 24 found evidence of a folded structure at the surface of polyethylene lamellae in the XPS valence band. In our previous papers, [16][17][18]20 we used syndiotactic model molecules for analysis of XPS of polymers, because we found that the tacticity had little effect on the calculated energy structure, in contradiction to the results of other workers. 23,24 In previous studies, [19][20][21][22] we showed that earlier workers used Koopmans' theorem and the δ-SCF method to analyze the photoelectron spectra of polymers.…”
Section: Introductioncontrasting
confidence: 56%
“…found evidence of a folded structure at the surface of polyethylene lamellae in the XPS valence band. In our previous papers, , we used syndiotactic model molecules for analysis of XPS of polymers, because we found that the tacticity had little effect on the calculated energy structure, in contradiction to the results of other workers. , …”
Section: Introductionmentioning
confidence: 57%
See 1 more Smart Citation